2016
DOI: 10.1016/j.bmhimx.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Instruments to measure the quality of life in patients with oral mucositis undergoing oncological treatment: a systematic review of the literature

Abstract: The evaluation of the QoL in patients with OM is a difficult scenario because of its multiple variables. The knowledge of this relationship is limited because general instruments of oral health or cancer therapy are commonly used for evaluation. However, valid instruments are already available for estimating the impact of OM on the QoL from the patient's perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“… 19 Increasing advocacy has emerged for PROMs being integrated into clinical practice and research, especially in supportive cancer care as it is well documented that clinicians tend to under-report on the prevalence, emergence and severity of treatment side effects, including mucositis. 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 However, given the dynamic nature of mucositis and an individual's perceived symptom burden, especially during treatment and its recovery, PROMs should be collected frequently, which may result in inflated intra-individual variation or “response shifts'. 17 Response shifts can be identified through patterns in longitudinal studies and incorporating measures of response shift can be valuable in assessing true change in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Increasing advocacy has emerged for PROMs being integrated into clinical practice and research, especially in supportive cancer care as it is well documented that clinicians tend to under-report on the prevalence, emergence and severity of treatment side effects, including mucositis. 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 However, given the dynamic nature of mucositis and an individual's perceived symptom burden, especially during treatment and its recovery, PROMs should be collected frequently, which may result in inflated intra-individual variation or “response shifts'. 17 Response shifts can be identified through patterns in longitudinal studies and incorporating measures of response shift can be valuable in assessing true change in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…While there are a variety of options available for mucositis assessment, these tools vary considerably in their complexity and degree of validation, 7 , 13 with no clear guidance on when and how they should be used. This heterogeneity has undoubtedly impacted the translation of clinical research into clinical practice, with varying adoption of mucositis assessment tools complicating evidence synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ]. The Oral Mucositis Weekly Questionnaire-Head and Neck Cancer (OMWQ-HN) is another instrument that measures the impact of oral mucositis on symptoms such as mouth and throat pain and also its effects on well-being and function [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that affected patients demonstrate decreased physical and emotional wellbeing compared with patients with cancer without mucositis (Cheng, 2007, Kim et al, 2012), including higher rates of depression (Gutiérrez-Vargas et al, 2016). Affected individuals also have a significantly higher risk of associated severe pain and weight loss >5% (Lalla et al, 2008).…”
Section: Traditional Chemotherapymentioning
confidence: 99%